Improving Early Childhood Basic English Vocabulary Recognition Skills through the Mystery Box Game for Group B Children at RA Al-Kautsar - Anastasya, Anastasya (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Foreign language learning, particularly English, needs to be introduced from an early age, as this period marks a crucial stage in rapid language development. However, in reality, many young children still struggle to recognize and pronounce basic English vocabulary. This study aims to improve the ability of children aged 5–6 years to recognize basic English vocabulary through the Mystery Box game. The research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles consisting of three meetings each. The research subjects were 15 Group B children at RA Al-Kautsar. The findings revealed that the implementation of the Mystery Box game significantly enhanced children’s vocabulary skills. Prior to the intervention, only 27% of the children demonstrated understanding of basic vocabulary, while after the second cycle, 93% of the children achieved the “Very Well Developed” category. Therefore, the Mystery Box game proved to be an effective medium for improving early childhood mastery of basic English vocabulary.